2010
DOI: 10.1007/s00227-010-1513-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on invertebrate settlement at volcanic CO2 vents

Abstract: We present the Wrst study of the eVects of ocean acidiWcation on settlement of benthic invertebrates and microfauna. ArtiWcial collectors were placed for 1 month along pH gradients at CO 2 vents oV Ischia (Tyrrhenian Sea, Italy). Seventy-nine taxa were identiWed from six main taxonomic groups (foraminiferans, nematodes, polychaetes, molluscs, crustaceans and chaetognaths). Calcareous foraminiferans, serpulid polychaetes, gastropods and bivalves showed highly signiWcant reductions in recruitment to the collecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
172
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(196 citation statements)
references
References 45 publications
19
172
5
Order By: Relevance
“…Used carefully, areas naturally enriched in CO 2 make ideal natural laboratories for investigating such evolutionary questions. Cigliano et al [43] found species-specific patterns of settlement in invertebrates along CO 2 gradients in this vent system, mirrored by patterns of presence/absence and abundance of adults of polychaete species in the hard bottom community [43,45], potentially indicating the presence of adaptation or acclimatization. In particular, around the CO 2 vents of Ischia, some polychaete species maintain high densities along pCO 2 gradients or even increase in density the closer they are to the vents.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Used carefully, areas naturally enriched in CO 2 make ideal natural laboratories for investigating such evolutionary questions. Cigliano et al [43] found species-specific patterns of settlement in invertebrates along CO 2 gradients in this vent system, mirrored by patterns of presence/absence and abundance of adults of polychaete species in the hard bottom community [43,45], potentially indicating the presence of adaptation or acclimatization. In particular, around the CO 2 vents of Ischia, some polychaete species maintain high densities along pCO 2 gradients or even increase in density the closer they are to the vents.…”
Section: Introductionmentioning
confidence: 68%
“…The first three dominate the most intense venting areas [43,45] and are commonly associated with rocky, shallow, vegetated habitat in the Mediterranean and with Posidonia oceanica (L.) Delile, 1813 seagrass beds [47][48][49]. P. dumerilii and S. prolifera are mesoherbivores, whereas A. mediterranea is a filter feeder.…”
Section: Materials and Methods (A) Selection Of Sensitive And Tolerantmentioning
confidence: 99%
See 1 more Smart Citation
“…Volcanic CO 2 seeps and areas of CO 2 upwelling have been described worldwide in temperate (Calosi et al 2013;Cigliano et al 2010;Hall-Spencer et al 2008;Inoue et al 2013;Johnson et al 2012;Porzio et al 2011) and tropical (Fabricius et al 2011(Fabricius et al , 2014Johnson et al 2012;Noonan et al 2013;Russell et al 2013;Uthicke and Fabricius 2012;Uthicke et al 2013) regions. So far, studies suggest reduced pH at CO 2 seeps in PNG lead to a decline in coral diversity with structurally complex species being particularly affected, and reduced taxonomic richness and density of coral juveniles, and low cover of crustose coralline algae (Fabricius et al 2011(Fabricius et al , 2014.…”
mentioning
confidence: 99%
“…Studies conducted in the natural vent system at Ischia, Italy, indicated that the settlement and colonization of mollusks and microfauna showed high reductions in recruitment in the acidified stations (Cigliano et al, 2010;Ricevuto et al, 2012;Milazzo et al, 2014). In experiments in which juvenile pen shells Pinna nobilis were transplanted to Ischia for 45 days, decreases in survival, growth, and oxygen consumption were found.…”
Section: Comparison With Other Ocean Acidification Studiesmentioning
confidence: 99%